Transcription Profiling of Malaria-Naïve and Semi-immune Colombian Volunteers in a Plasmodium vivax Sporozoite Challenge. - Monica L Rojas-Peña; Andres Vallejo; Sócrates Herrera; Greg Gibson; Myriam Arévalo-Herrera (Public Library of Science (PLoS), 2015)
BACKGROUND:Continued exposure to malaria-causing parasites in endemic regions of malaria induces significant levels of acquired immunity in adult individuals. A better understanding of the transcriptional basis for this acquired immunological response may provide insight into how the immune system can be boosted during vaccination, and into why infected individuals differ in symptomology. METHODOLOGY/PRINCIPAL FINDINGS:Peripheral blood gene expression profiles of 9 semi-immune volunteers from a Plasmodium vivax malaria prevalent region (Buenaventura, Colombia) were compared to those of 7 naïve individuals from a region with no reported transmission of malaria (Cali, Colombia) after a controlled infection mosquito bite challenge with P. vivax. A Fluidigm nanoscale quantitative RT-PCR array was used to survey altered expression of 96 blood informative transcripts at 7 timepoints after controlled infection, and RNASeq was used to contrast pre-infection and early parasitemia timepoints. There was no evidence for transcriptional changes prior to the appearance of blood stage parasites at day 12 or 13, at which time there was a strong interferon response and, unexpectedly, down-regulation of transcripts related to inflammation and innate immunity. This differential expression was confirmed with RNASeq, which also suggested perturbations of aspects of T cell function and erythropoiesis. Despite differences in clinical symptoms between the semi-immune and malaria naïve individuals, only subtle differences in their transcriptomes were observed, although 175 genes showed significantly greater induction or repression in the naïve volunteers from Cali. CONCLUSION/SIGNIFICANCE:Gene expression profiling of whole blood reveals the type and duration of the immune response to P. vivax infection, and highlights a subset of genes that may mediate adaptive immunity.